Isu Ketidakadilan dan Diskriminasi dalam Dunia Olahraga: Diskriminasi Olahraga - Takdir, Muh; Rahim, Muh Yusuf; Hudain, Muh Adnan; Alwi, Alimin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines the main forms of discrimination, including gender inequality, racial bias, economic barriers, challenges faced by athletes with disabilities, the impact of the industrialisation of sport, and the influence of the Relative Age Effect (RAE). The method used is a literature study covering academic research, international agency reports, policy documents, and case studies. The results of the study show that gender inequality is still evident in the distribution of resources, competition opportunities, leadership positions, and media coverage. Racial bias arises through stereotypes, subjective coaching assessments, and economic inequality. Athletes from low-income families face limitations in accessing quality coaching, facilities, and competitions, while athletes with disabilities often face barriers in accessing adequate facilities and support. RAE also contributes to creating indirect but persistent inequalities in athlete development. These various forms of discrimination have an impact on athletes' psychological well-being, career opportunities, and the effectiveness of sports organisation management. The research findings emphasise the need for inclusive policies, anti-discrimination training, equal access to facilities, transparent selection processes, and more balanced media coverage